Distribution patterns of antioxidants in the organs of anadromous fish Tenualosa ilisha (Hamilton, 1822)—a profiling in different age groups for future application in anti-aging - Chakraborty, Hena; Das, Basanta Kumar; Chakraborty, Nabanita; Sahoo, Amiya Kumar; Maity, Joydev (Frontiers in Marine Science, 2024)
Antioxidants play a crucial role in maintaining health by scavenging free radicals that causes cellular damage and accelerates aging and disease. The present study focuses on the antioxidant levels in various organs of Hilsa fish, both male and female, with a weight range of 50 g to 780 g collected from the Hooghly River in the lower Gangetic plain. The study utilized commercially available free radicals such as, viz., 2,2′-azinobis-[3-ethyl-benzothiazoline-6-sulfonic acid] and ferric reducing antioxidant potential to measure the scavenging activity. The results indicated that female Hilsa fish possess higher levels of antioxidants (93.79 ± 0.26) compared to male counterparts (84.50 ± 0.65) in all organs, with levels increasing proportionally with weight. Interestingly, in males, the serum antioxidant profile was higher in the lower weight group (50–100 g), whereas, in females, the highest antioxidant activity was observed in the weight range of 300 g to 400 g. The present study was attempted for the first time to characterize the antioxidant distribution pattern in the different organs of Hilsa. These findings suggest that Hilsa fish organs, including serum, contain high levels of antioxidants that could significantly benefit human nutrition and potentially will contribute to anti-aging effects by incorporating Hilsa to their diet, which needs further clinical study.